Cold plasma-induced ovalbumin amyloid fibrils: Morphological characteristics and stability on astaxanthin-loaded high internal phase emulsions - Chang Liu; Pan-Pan Tang; Xiu-Bin Liu; Najla AlMasoud; Taghrid S. Alomar; Rana Muhammad Aadil; Jun-Hu Cheng; Zhi-Wei Liu (Food Chemistry: X)
The morphological characteristics of cold plasma (CP)-induced ovalbumin (OVA) amyloid fibrils (OAFs) and their ability to stabilize astaxanthin-loaded high internal phase emulsions (HIPEs) were investigated. The results indicated that CP treatment significantly accelerated OVA fibrillization by inducing its globular structure unfolding and polypeptide cleavage, leading to the rapid formation of short, worm-like fibrils within 10 min of fibrillation. Compared to untreated OVA, which had a diameter of 18.65 ± 6.47 nm, the length of OVA worm-like fibrils progressively increased from 69.17 ± 23.84 nm (10 min) to 114.94 ± 38.04 nm (8 h) before decreasing to 92.24 ± 36.22 nm (24 h). The ability of OVA to stabilize HIPEs was significantly improved following fibrillation. Notably, the shorter fibrils of OAFs-10 min and OAFs-24 h exhibited superior stability in HIPEs compared to the longer fibril of OAFs-8 h. The reason may be ascribed to the robust interface adsorption ability of OAFs-10 min and OAFs-24 h with shorter length, generating a dense and thick interfacial layer in the oil/water emulsion (maximum 11.57 ± 1.98 %), as confirmed by confocal laser scanning microscopy (CLSM) imaging and interface protein adsorption analysis (maximum 31.61 ± 2.49 %), thereby preventing droplet coalescence. Additionally, HIPEs stabilized by OAFs-10 min exhibited a higher oil fraction (82.5 %), superior ionic (1200 mM) and thermal stability (100 °C), and greater astaxanthin retention (91.55 ± 1.97 %, 1200 mM) compared to those stabilized by other OAFs. Meanwhile, HIPEs stabilized by OAFs-24 h exhibited enhanced stability under freeze-thaw cycles and centrifugation, with centrifugal stability constant (Ke) of 16.18 ± 4.78 %.